Geographical Variation in Peritoneal Dialysis Catheter Insertion and Initiation within the United States. Issue 6 (November 2016) - Patel, Achint; Shah, Harshil; Patel, Shanti; Nadkarni, Girish N.; Uribarri, Jaime
Peritoneal dialysis (PD) is an effective but underutilized renal replacement therapy modality. There are limited data regarding geographical variation in PD catheter insertion and utilization of PD as a first renal replacement therapy in the United States. We explored the variation in catheter insertion and initiation of PD utilizing 2 large, nationally representative databases. The incidence of catheter insertion differed significantly by geographical region, being highest in the South (7.30/100 end-stage renal disease [ESRD] patients; 95% confidence [CI] interval 6.78 – 7.81) and lowest in the West (5.91/100 ESRD patients; 95% CI 5.43 – 6.38). Peritoneal dialysis initiation also differed by region, being highest in the West (7.10/100 ESRD patients; 95% CI 6.83 – 7.30) and lowest in the Northeast (5.12/100 ESRD patients; 95% CI 4.87 – 5.30). Interestingly, the Northeast region, with the lowest rate of PD utilization, had the highest number of nephrologists per population (3.95/100, 000 persons), and the West, with the highest PD utilization, had the lowest number of nephrologists (2.54/100, 000 persons). Reasons for this variation should be explored further and efforts should be made to standardize PD implementation throughout the United States.